2011
DOI: 10.1021/jp210822s
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Properties of Hyperbranched Polythiophenes

Abstract: Branched conjugated architectures should possess the advantage of isotropic charge transport compared to conventional linear conjugated polymers, as for example poly(3-hexylthiophene) (P3HT) which is commonly used in organic solar cells. This contribution investigates the optoelectronic properties of branched poly(thiophene)s p3T and p4T synthesized in a straightforward one-pot procedure by oxidative coupling of branched trithiophene and tetrathiophene monomers with FeCl(3). These polymers can be regarded as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…The performance of the synthesized materials was further investigated in bottom gate bottom contact transistors which showed a reasonable field effect charge carrier mobility up to 4.3 × 10 −5 cm 2 V −1 s −1 for P(3T) and 2.5 × 10 −4 cm 2 V −1 s −1 for P(4T) . This was explained by the lower branching density of P(4T) compared to P(3T): In case of P(4T) there is apparently less intramolecular twisting and therefore facilitated intra‐ and intermolecular charge transport.…”
Section: Branched Polythiophenesmentioning
confidence: 97%
See 2 more Smart Citations
“…The performance of the synthesized materials was further investigated in bottom gate bottom contact transistors which showed a reasonable field effect charge carrier mobility up to 4.3 × 10 −5 cm 2 V −1 s −1 for P(3T) and 2.5 × 10 −4 cm 2 V −1 s −1 for P(4T) . This was explained by the lower branching density of P(4T) compared to P(3T): In case of P(4T) there is apparently less intramolecular twisting and therefore facilitated intra‐ and intermolecular charge transport.…”
Section: Branched Polythiophenesmentioning
confidence: 97%
“…With a molecular weight of 7392 g mol −1 the largest reported all‐thiophene dendrimer is the 90T‐dendrimer synthesized in the same group . This monodisperse polymer exhibits an absorption maximum at 387 nm and lowered HOMO and LUMO levels (–5.2 and –3.0 eV, respectively) compared to P3HT (–5.1 and –2.8 eV, respectively) . Power conversion efficiencies up to 1.7% were achieved in combination with PC[61]BM in organic solar cells.…”
Section: Structurally Well‐defined Branched Thiophenes: From Small Momentioning
confidence: 99%
See 1 more Smart Citation
“…they are simply called branching defects. Although the influence of branching on conjugated polythiophenes has been studied previously, the monomers either did not contain alkyl chains or β,β‐linkages instead of α,β‐linkages were studied making the direct comparison with DArP‐produced β‐defects difficult.…”
Section: Structural Defects In Darp Polymersmentioning
confidence: 99%
“…The PCE values of solar devices based on B-P3HT:PC 60 BM were 0.13-2%. Mangold et al reported two hyperbranched PTs using 2,3-dithienylthiophene or 2,3,5-trithienylthiophene as bridging cores [14]. The In this study, we propose a new approach to synthesize the hyperbranched PT M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT derivatives by introducing perylene bisimide (PBI) or soft alkyl spacer as bridging moieties.…”
Section: A N U S C R I P Tmentioning
confidence: 99%